Using social media for community consultation and public disclosure in exception from informed consent trials. Issue 6 (June 2016) - Stephens, Shannon W.; Williams, Carolyn; Gray, Randal; Kerby, Jeffrey D.; Wang, Henry E.; Bosarge, Patrick L.
Abstract : BACKGROUND: The US Food and Drug Administration and the Department of Health and Human Services outline regulations allowing an exception from informed consent (EFIC) for research conducted in an emergency setting. Acute care clinical trials using EFIC must include community consultation and public disclosure (CC/PD) activities. We describe our experience using social media to facilitate the CC/PD process in two trauma resuscitation clinical trials. METHODS: We conducted local CC/PD activities for two multicenter trauma clinical trials, Pragmatic, Randomized Optimal Platelet and Plasma Ratios (PROPPR) and Prehospital Tranexamic Acid Use for Traumatic Brain Injury (ROC-TXA). As part of the CC/PD process, we developed research study advertisements using the social media Web site Facebook. The Facebook advertisements directed users to a regional study Web site that contained trial information. We targeted the advertisements to specific demographic users, in specific geographic areas. We analyzed the data using descriptive statistics. RESULTS: During the study periods, the PROPPR Facebook advertisement was displayed 5, 001, 520 times (12 displays per target population) with 374 individuals selecting the advertisement. The ROC-TXA Facebook advertisement was displayed 3, 806, 448 times (8 per target population) with 790 individuals selecting the advertisement. Respondents to both Facebook advertisements were mostly male (52.6%), with the highest proportion between the ages 15 years and 24 years (28.2%). Collectively, 26.9% of individuals that clicked on the Facebook advertisement spent more than 3 minutes on the study Web site (3–49 minutes). Commonly accessed Web pages were "contact us" (PROPPR, 5.5%; ROC-TXA, 7.7%), "study-specific FAQs" (PROPPR, 2.4%; ROC-TXA, 6.7%), and "opt out of research" (PROPPR, 2.5%; ROC-TXA, 3.8%). Of 51 total individuals viewing the opt out of research information (PROPPR, 19; ROC-TXA, 32), time spent on that specific page was modest (PROPPR, 62 seconds; ROC-TXA, 55 seconds), with no individuals requesting to opt out of either study participation. CONCLUSIONS: In clinical trauma trials using EFIC, social media may provide a viable option for facilitating the CC/PD process.